2002
DOI: 10.1093/mutage/17.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanol treatment on metabolic activation and detoxification of esophagus carcinogenic N-nitrosamines in rat liver

Abstract: In order to elucidate the mechanism underlying enhancement by ethanol of N-nitrosodiethylamine (DEN)- and N-nitrosomethylbenzylamine (NMBA)-induced esophageal tumorigenesis in rats, hepatic levels of cytochrome P-450 (CYP) enzymes, mutagenic activation of several N-nitrosamines and three kinds of UDP-glucuronyltransferase (UDPGT) activities were assayed in F344 rats. Immunoblot analyses of microsomal CYP proteins revealed induction of CYP2E1 (approximately 2-fold), but not CYP2B1/2, 1A1/2 or 3A2, by treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…As another alkylating agent, DEN was used in this study, and DEN is metabolically activated mainly by CYP2E1 to alkylate DNA (Mori et al, 2002). In this study, DEN increased DNA migration at pH 12.1 and pH 13, and the largest portion of the DNA migration was considered to be SSBs, because the DNA migration at pH 13 at 3 hr after DEN-treatments was comparable to or slightly more than at pH 12.1.…”
Section: Discussionmentioning
confidence: 95%
“…As another alkylating agent, DEN was used in this study, and DEN is metabolically activated mainly by CYP2E1 to alkylate DNA (Mori et al, 2002). In this study, DEN increased DNA migration at pH 12.1 and pH 13, and the largest portion of the DNA migration was considered to be SSBs, because the DNA migration at pH 13 at 3 hr after DEN-treatments was comparable to or slightly more than at pH 12.1.…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, it is possible that the lack of detectable CYP1A protein in fetal HSC could be explained by alternative CYP1A1 gene splicing during translation that occurs in rat and human brain (Chinta et al, 2005). Similar to CYP1A2, CYP2E1 is expressed at low levels in fetal liver with up-regulation of expression occurring at birth (Mori et al, 2002). CYP2E1 is the highaffinity liver P450 isoform involved in the metabolism and activation of several aliphatic and aromatic halogenated hydrocarbons (Hines and McCarver, 2002;Gonzalez, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism for this effect is unknown, one study suggested that it was dependent on the presence of hepatic Kupfer cells (Kardon et al, 2002). On the other hand another study that involved adding 10% alcohol to the drinking water of rats showed no effect on hepatic bilirubin, nitrophenol or testosterone glucuronidation (Mori et al, 2002). …”
Section: Interindividual Variability In Activity Of the Major Ugt Isomentioning
confidence: 99%